Peran Arbitrase di Bank Syariah dalam penyelesaian Sengketa - hasanah, Ulfa (Sharia Faculty Islamic Economic Law Study Department, 2021)
The Indonesian muamalah arbitration board was officially established on October 21 1993. Based on the decision letter of the Indonesian Ulama Council no. Kep/09/MUI/XXI/2003 dated December 24, 2003, in the name BAMUI was changed to the National Sharia arbitration body (BASYARNAS). The application of arbitration as a dispute resolution in Islamic banks through the national Sharia arbitration board is a research called normative juridical. Every sharia bank activity must comply with the fatwa of the National Sharia Council of the Indonesian Ulema Council, as well as the resolution of disputes in sharia banks. The National Sharia Arbitration Board has procedural regulations in accordance with the provisions of law number 30 of 1999 concerning arbitration and alternative dispute resolution.